A Model of Election Supervision Based on Village Judicial Institutions; A Review of Legal Anthropology in Madura - Da Silva, Eugenia Brandao; Ali, Mahrus; Rohman, Khabib Syaikhu; Mashud, Mashud (TRUNOJOYO LAW REVIEW, 2024)
The General Election Law has placed villages at the forefront of the election monitoring system by establishing Village Panwaslu. However, it still needs to be fully able to unravel the complexity of the election monitoring system. This study aims to strengthen the election supervision system so that all electoral issues can be resolved at the village level. This research uses normative legal research methods that focus on the reconstruction and institutionalization of the election supervision system at the village level through the synergy of village judicial institutions. The result of the research is that the design of election supervision at the village level, which only places one member, has yet to resolve the many burdens of election supervision fully. Although Article 448 paragraph (3) of the Election Law authorizes the community to monitor actively, it has proven not optimal because there is no clear legal protection for the participatory monitoring system. The weakness of the monitoring system can be strengthened through 1) The establishment of Village Panwaslu members that involve village judicial institutions consisting of Babinkantibmas, Babinsa, and community leaders; 2) Expanding the authority of the Village Panwaslu to resolve disputes over the election process at the village level.